Islam dan Kearifan Lokal Sunda ( Tradisi 10 Muharam Bubur Suro di Sumedang) - Putri, Novi Andika (Historia Madania: Jurnal Ilmu Sejarah, 2019)
Before Religion in Indonesia was Islam, they have embraced Hinduism and Buddhism. Afterwards, Islam came to Indonesia around 7 century. This is one of the reasons why Indonesia has acculturation of culture between cultures of Hindu-Buddha and Islam. At Indonesia, especially at Sumedang has a unique culture that interesting is researched. The culture is Bubur Suro that does every 10 Muharam. Bubur Suro had a long history from an ancestor. theÂ chieftain said that the way to commemorate the Islamic new year and to remember the events of the Prophet Nuh and the Flood. In addition, this is enforced, with motivation to conserve ancestor tradition. This written uses method of history consists of heuristic, criticism, interpretation and historiography. In this research, it was revealed that the Sumedang community, especially Negarawangi village, the majority of followers of Islam who still maintain Sundanese ancestral traditions, so that every 10 Muharam they celebrate the celebration of Maulud Nabi and also the Bubur Suro ceremony. In conclusion, Islam and the Sundanese tradition in the Bubur Suro ceremony become a form of acculturation that is still maintained in the Rancakalong between Islam and the Sundanese tradition. Â  Keywords: budaya, muharam, sumedang